Pathways toward Climate-Neutral Red Meat Production - Bradley Ridoutt (Methane, 2024)
Ruminant livestock industries can support the climate stabilization ambitions of the Paris Agreement through interventions that reduce GHG emissions (predominantly biogenic methane) and sequester carbon in landscapes. This study explored pathways for the Australian red meat industry (grazing, feedlot finishing, and domestic processing) to become climate neutral, whereby the radiative forcing (RF) footprint is plateaued and there is no additional forcing contribution. Emissions timeseries (CO2, N2O, CH4) were compiled for 1990 to 2020 and projected to 2030 under a business-as-usual scenario (including an 18% increase in sheep and 13% increase in beef cattle) and with a range of production system and vegetation management interventions. The RF footprint peaked in 2018 at 7.13 mW/m2 and decreased to 7.07 mW/m2 in 2020. With the future expansion of the herd/flock and under business-as-usual conditions, the RF footprint is projected to increase by 2.8% by 2030. However, with a combination of interventions, production has the potential to increase with a decreasing RF footprint, a condition that can be described as climate neutral. The Australian red meat industry has made an historical contribution to global RF increase. However, with ongoing RF management, it is possible to increase food production within climate-neutral limits.